Developing computer-support learning environments in vocational education: A socio-cultural approach to the study of pilot projects - Perret, Jean-Francois; Grossen Peretti, Michèle (My University, 2005)
In this paper, we present a research which was aimed at evaluating the use of platforms for e-learning in twenty vocational schools in Switzerland. The research has been carried out over a two-year period (2002-2004) in which each of these schools developed a pilot project that gave them the opportunity of experimenting various forms of computer-support learning environments in order to meet their different training needs. Drawing upon a socio-cultural approach, our research questions focus upon the meaning that the various actors give to their pilot projects; the way in which they make sense and appropriate new tools of communication; the influence of these tools on educational practices; the organisational and technological conditions that enable the realisation of a school project; the various resources used (or not) by the project teams. In order to answer these questions, the method puts emphasis upon a qualitative approach: interviews with the leaders of the projects and all the teachers involved in the projects; participation in the meetings of the project teams; observation of training situations; analysis of the documents and e-mails which were exchanged through the platforms; questionnaires addressed to the students and teachers involved in the school projects. The results presented in this paper will concern two different aspects. First, we shall describe the educational practices that have been developed in the new learning environments that the schools have experimented. Second, we shall analyse a series of dimensions which account for some positive outcomes in the school projects.
, 2005